Phytochemical Composition and Antibacterial Activity of Barringtonia asiatica (L.) Kurz Fruit Peel Extracts against Staphylococcus aureus and Escherichia coli - Sriwulandari; M. Deddy Harfiansyah (Sciences and Clinical Pharmacy Research Journal, 2026)
The present study investigated the phytochemical constituents and antibacterial potential of methanol, ethyl acetate, and n-hexane extracts obtained from the fruit peel of Barringtonia asiatica against the bacteria Staphylococcus aureus and Escherichia coli. The powdered peel material was initially extracted through a maceration process using methanol as the solvent, after which the extract was fractionated with ethyl acetate and n-hexane to obtain different polarity fractions. Qualitative phytochemical screening was conducted to determine the presence of secondary metabolites, whereas antibacterial activity was assessed using the agar diffusion technique at concentrations ranging from 100 to 500 mg/ml. The phytochemical evaluation revealed that the methanol extract contained several bioactive compounds, including flavonoids, tannins, and terpenoids. In the antibacterial test, the ethyl acetate fraction demonstrated the highest inhibitory effect on both test microorganisms at a concentration of 500 mg/ml, producing inhibition zones of 16.42 mm against S. aureus and 11.37 mm against E. coli. Meanwhile, the methanol extract produced inhibition zones of 13.30 mm and 10.63 mm, respectively. The n-hexane fraction exhibited comparatively weaker activity, with inhibition zones measuring 7.45 mm against  S. aureus and 7.32 mm against E. coli. Overall, these findings suggest that extracts  derived from the fruit peel of B. asiatica possess antibacterial properties, with the  ethyl acetate fraction showing the most pronounced inhibitory activity among  the tested extracts.